Hydrogen Production Analysis: Prospects for Ukraine (Agricultural Engineering, 2021)
Over the last few years, hydrogen energy has shifted from a little-studied field to the main one with which leading western countries associate the prospects of their national economies. The reasons are the unprecedented pace of development of hydrogen technologies. It turned out that they are able to provide significant reductions in greenhouse gas emissions, and thus bring closer the solution to the problem of global climate change. The first and foremost purpose of our investigation is to reveal that our country has ample opportunities to become the main supplier of hydrogen to the EU market, overtaking North Africa in the competition. Using the methods, authors studied the targets of the European funds towards development of energy production from biohydrogen, studied the potential for the implementation of hydrogen projects, possibilities of financing them and a potential ability of Ukraine to form internal and external markets for hydrogen energy. One of the main issues of Ukraine's possible participation in Europe's hydrogen energy program as a supplier and producer of renewable hydrogen is the possibility of its technically safe and cost-effective transportation to EU countries. As a conclusion to the authors’ research, the path of the hydrogen industry development in Ukraine will help to receive additional investments in the Ukrainian economy for creation of new capacities for "green" hydrogen production. In return, Europe will receive research and evolution of the bioenergy component of the economy, which will permit the safe transition of Europeans to an affordable, competitive, and stable energy system.